Necrotizing Enterocolitis in a Dutch Cohort of Very Preterm Infants: Prevalence, Mortality, and Long-Term Outcomes - Imren, Ceren; Vlug, Lotte E.; de Koning, Barbara A. E.; Diertens, Tessa; Snel, Heleen E.; Suurland, Jill; Swarte, Renate M. C.; Vermeulen, Marijn J.; Keyzer-Dekker, Claudia M. G. (European Journal of Pediatric Surgery, 2022)
Introduction To improve counseling of parents and to guide care strategies, we studied the disease course and outcomes of necrotizing enterocolitis (NEC) up to 2 years of corrected age (CA) from a multidisciplinary perspective.Materials and Methods This was a retrospective cohort study in preterm infants (birth weight < 1,500 g, gestational age < 32 weeks), diagnosed with NEC (Bell's stage ≥ II) from 2008 through 2020. Data on prevalence, mortality, surgery, intestinal failure (IF), growth, and neurodevelopment at 2-year follow-up were separately analyzed for medically and surgically treated children.Results Of 3,456 preterm infants, 200 (6%) were diagnosed with NEC, of whom 135 developed an indication for surgery within 7 days after the diagnosis; 28/135 died before surgery, and 37/107 died after an open-and-close procedure. An enterostomy was constructed in 62 patients and an end-to-end anastomosis in 15. The postoperative course was described for 77 patients, of whom 23 developed surgical complications (12/23 incisional hernias, 9/23 anastomotic strictures), 13/77 a short bowel, and 25/77 IF. Sixty-day survival after birth for medical NEC patients was 88% (hazard ratio [HR]: 0.698; p = 0.318), and for surgically treated NEC patients was 40% (HR: 3.729; p < 0.001). At 2-year follow-up, one patient received parenteral nutrition. Severe delay in weight for age, motor, and cognitive development was seen in 3, 6, and 2%, respectively.Conclusion In this cohort, the mortality rate was high, especially in surgically treated NEC patients. The surgical complication rate is comparable to previous studies, but in surviving patients, persisting IF and severe delay in growth and neurodevelopment at 2 years CA were relatively rare.
Keywords: infant; surgery; medical treatment; intestinal failure; neurodevelopment